A.k.a. Cassius Clay [videorecording (DVD)]. - Jacobs, Jim; Ali, Muhammad, 1942-2016; Kiley, Richard; D'Amato, Cus (Metro Goldwyn Mayer Home Entertainment, 2000)
After Cassius Clay wins a gold medal in the Olympics, several millionaires from Kentucky invest in him and his professional career begins. Clay fights Henry Cooper, Cleveland Williams, Floyd Patterson, and finally, in 1964, Sonny Liston for the heavyweight championship. In the meantime, Clay has been influenced by Malcolm X, converts to the Muslim faith and changes his name to Muhammad Ali. Because of his religious convictions, Ali refuses induction into the US Army in 1967 but is denied conscientious objector status. The NY State Athletic Commission strips him of his title and he is barred from the ring.